Genetic association and bidirectional Mendelian randomization for causality between gut microbiota and six lung diseases - Su, Yue; Zhang, Youqian; Xu, Jinfu (Frontiers in Medicine, 2023)
Increasing evidence suggests that intestinal microbiota correlates with the pathological processes of many lung diseases. This study aimed to investigate the causality of gut microbiota and lung diseases.Methods: Genetic information of intestinal flora and lung diseases (asthma, chronic bronchitis, chronic obstructive pulmonary disease (COPD), interstitial lung disease (ILD), lower respiratory tract infection (LRTI), pulmonary arterial hypertension (PAH)) and lung function was obtained from UK Biobank, FinnGen and additional studies. A Mendelian randomization (MR) analysis was conducted to explore the causal association between gut microbiota and lung diseases.The genetic liability to lung diseases may be associated with the abundance of certain microbiota taxa. Specifically, genus. Prevotella (p=0.041) was related to a higher risk of asthma, the family. Defluviitaleaceae (p=0.002) and its child taxon were identified as a risk factor for chronic bronchitis, the abundance of the genus. Prevotella (p=0.020) was related to a higher risk of ILD, family.Coriobacteriaceae (p=0.011) were identified to have a positive effect on the risk of LRTI, genus Lactobacillus (p=0.0297) has been identified to be associated with an increased risk of PAH, whereas genus. Holdemanella (p=0.0154) presented a causal decrease in COPD risk, order. Selenomonadales were identified to have a positive effect on the risk of FEV1(p=0.011). The reverse TSMR analysis also provided genetic evidence of reverse causality from lung diseases to the gut microbiota.This data-driven MR analysis revealed gut microbiota was causally associated with lung diseases, providing genetic evidence for further mechanistic and clinical studies to understand the crosstalk between gut microbiota and lung diseases.